CYBERPRAGMATICS OF POLITENESS IN NETIZENS’ COMMENTS ON THE INDONESIAN PRESIDENT’S INSTAGRAM POSTS - Akram Budiman Yusuf; Firdhani Resha (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
This study aims to reveal the content of negative politeness in netizens' speech in response to the President of Indonesia’s Instagram posts for the 2024–2029 period, highlighting the disparity between expected norms of respectful digital interaction and the often impolite or aggressive language used in political commentaries. The approach used is descriptive qualitative based on pragmatic theory, especially Brown and Levinson's politeness theory, and supported by a cyberpragmatic approach. Data in the form of netizens' verbal speech was collected using note-taking and screen capture techniques, then analyzed using the Miles and Huberman interactive model. The results of the study show that many comments contain violations of negative politeness, such as unmitigated direct speech, sharp criticism, and even sarcasm that threatens the face of the interlocutor. However, some netizens still show politeness strategies by conveying criticism in a subtle and implicit manner. This phenomenon reflects changes in communication patterns on social media, which are characterized by freer expression but tend to ignore politeness norms. These findings reinforce the importance, especially in terms of language ethics, and open up space for the integration of a cyberpragmatic approach in learning Indonesian.